Rank-and-File Employees’ Awareness on the Programs and Services of a Social Health Insurance Corporation in the Philippines - Roldan, Maricris R.; Cruz, Myra Lee C. Dela; Oreta, Erliza M.; Guino, Ian Chester G.; Briones, Jesus; Soren, James (Inclusive Society and Sustainability Studies, 2023)
The rank-and-file employees of the subject social health insurance corporation (SHIC) should comprehensively understand its program and services as they are expected to provide timely, accurate, and relevant information to the members. This study was conducted to determine the awareness of employees on the programs and services of a SHIC in the Philippines. It focused on three aspects: membership, contribution, and benefits availment. This study also looked into the top queries received by employees and the channel or medium of communication where they primarily received the information. This descriptive-quantitative research used a structured questionnaire distributed to the 186 SHIC employees (Job Grades 5-10) in the different sectors of the corporation. Findings revealed that SHIC employees are generally somewhat aware of the three aspects of SHIC's programs and services. It was also found that the level of awareness of employees does not vary across job grade classifications. The most frequent inquiries received by SHIC employees revolved around membership processes such as ID/MDR issuance, membership registration, updating of dependents, and understanding benefits and deductions. Lastly, official social media platforms, meetings, interaction with colleagues, and direct communication from SHIC representatives were the organization's primary sources of information.  The recommendations forwarded in this study can enhance SHIC's services aligned with its mission of providing accessible and affordable healthcare in the country.